OH Density Measurements by Time‐Resolved Broad Band Absorption Spectroscopy in a He–H2O Dielectric Barrier Discharge with Small O2 Addition. Issue 3 (27th December 2013) - Martini, Luca Matteo; Dilecce, Giorgio; Scotoni, Mario; Tosi, Paolo; Benedictis, Santolo De
<x xml:space="preserve">Abstract</x> We have measured OH densities by time‐resolved broad‐band absorption spectroscopy in a He–H2O–O2 dielectric barrier discharge, with the aim to investigate the effect of water and oxygen addition on OH production. The results are examined in the light of literature data, in particular model calculations of reactive oxygen species (ROS) concentrations in a rf discharge with similar gas mixtures. Although relevant to different systems, the comparison is nevertheless interesting. At low water content and no oxygen a fair agreement is found with the model. The observed dependence on water and oxygen, at almost constant discharge power, is instead found to be smoother than the calculated one, probably because in our discharge the power invariance does not imply a constant production of OH.<inline-graphic xlink:href="ark:/27927/pgg4sxzdskw" content-type="ppap201300116-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />